Surgical treatment of a patient with multinodular goiter with compression syndrome of the neck and severe comorbid pathology - E. A. Ilyicheva (Вестник хирургии имени И.И. Грекова, 2020)
The study was to report a case of surgical treatment of multinodular cervicothoracic goiter complicated by compression syndrome of the neck (compression of the trachea, esophagus) with severe comorbid pathology.